2023
DOI: 10.3390/ijms241512235
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Anionic Chlorinated Dyes from Polluted Aqueous Streams Using Ionic Liquids and Their Subsequent Recycling

Barbora Kamenická,
Petr Švec,
Tomáš Weidlich

Abstract: The effect of ionic liquids on the separation of chlorinated anionic dyes such as Mordant Blue 9 (MB9) or Acid Yellow 17 (AY17) via ion exchange has been investigated in model aqueous solutions that simulate wastewater from the textile dyeing industry. The effect of ionic liquids chemical nature on the separation efficiency of mentioned dyes has been compared. It was found that especially ionic liquid based on quaternary ammonium salts comprising two or three long alkyl chains bound to the quaternary ammonium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…(b) The rapid formation of less polar ion pairs: The formation of water-insoluble ion pairs was discussed in Section 3.2. Separation of RB8 using ILs above and was also proved in our previous studies [44,45] using analytical techniques such as NMR. (c) (i) In the case of BC application, the better affinity of formed ion pairs to the BC surface: As Gray et al [59] suggested, the biochar-based sorbents show rather the non-polar nature of its surface.…”
Section: Co-action Of Ils and Alternative Sorbents For Rb8 Separationsupporting
confidence: 61%
See 4 more Smart Citations
“…(b) The rapid formation of less polar ion pairs: The formation of water-insoluble ion pairs was discussed in Section 3.2. Separation of RB8 using ILs above and was also proved in our previous studies [44,45] using analytical techniques such as NMR. (c) (i) In the case of BC application, the better affinity of formed ion pairs to the BC surface: As Gray et al [59] suggested, the biochar-based sorbents show rather the non-polar nature of its surface.…”
Section: Co-action Of Ils and Alternative Sorbents For Rb8 Separationsupporting
confidence: 61%
“…The better separation of RB8 using BAC can be caused by the better solubility of BAC in water and thus a better contact of BAC and RB8 dissolved in water. Based on these findings, BAC combines both sufficient aqueous solubility and the removal efficiency of acid halogenated pollutants such as RB8 dye; for more information, see our previous studies [32,44,45].…”
Section: Separation Of Rb8 Based On Ion Exchange Using Ilsmentioning
confidence: 89%
See 3 more Smart Citations